2000
DOI: 10.1023/a:1015301909441
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Antiamnestic effect of acyl-prolyl-containing dipeptide GVS-111 was demonstrated in rats with bilateral compression-induced damage to the frontal cortex. Both intraperitoneal and oral administration of the dipeptide improved retrieval of passive avoidance responses in rats with compression-induced cerebral ischemia compared to untreated controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Previous studies showed [6] that bilateral photochemically induced thrombosis of blood vessels in the prefrontal cortex of rats is followed by the development of focal ischemia. It spreads over the width of the cortex and is separated from the surrounding normal Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed [6] that bilateral photochemically induced thrombosis of blood vessels in the prefrontal cortex of rats is followed by the development of focal ischemia. It spreads over the width of the cortex and is separated from the surrounding normal Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In light of this, it is interesting to study the formation of Glu-AB during cerebral ischemic injury and evaluation of the role of these antibodies under conditions of brain damage. Bilateral ischemic injury to the prefrontal cortex in rats was used as an experimental model of cerebral ischemic injury [6]. In rats, the anterior part of the prefrontal neocortex and the hippocampus are known to play a role in integrative activity of the brain associated with learning and memory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments were performed on adult male Wistar rats weighing 180-200 g. Bilateral focal ischemic injury of the prefrontal cortex was produced by the method of photochemical thrombosis [8] with modifications of I. V. Viktorov [3]. The animals were intravenously narcotized with 300 mg/kg chloral hydrate and the head was fixed in a stereotaxis.…”
Section: Methodsmentioning
confidence: 99%
“…Στα πλαίσια της συνθετικής εργασίας της διατριβής, όπως αυτά οριοθετήθηκαν βάσει της στρατηγικής σχεδιασμού των νέων ενώσεων, η ιβουπροφαίνη συνδέθηκε μέσω αμιδικού δεσμού με υπόλοιπο L-προλίνης, που αναμένεται να προσδίδει στα μόρια νοοτρόπες ιδιότητες, καθώς δομικά ανάλογοι εστέρες ή αμίδια της προλίνης εμφανίζουν νοοτρόπο δράση, ενώ διπεπτίδια της προλίνης έχει βρεθεί ότι είναι περίπου 2000 φορές πιο ισχυρά νοοτρόπα από την πιρακετάμη (Gudasheva et al, 1996;Romanova et al, 2000). Προς το σκοπό αυτό συντέθηκε η ένωση 1 (σχήμα 3.1) και στη συνέχεια η καρβοξυλική ομάδα της προλίνης αμιδοποιήθηκε με αιθυλεστέρα της L-κυστεΐνης και κυστεαμίνη (ενώσεις 2 και 3 αντίστοιχα), γνωστά αντιοξειδωτικά χαμηλής τοξικότητας (Burner et al, 1999).…”
Section: γ) άλλοι παράγοντεςunclassified